Electromagnetic Imaging Mechanism And Algorithm Research Based on Volume Holographic Grating - Bao, Yuhui (My University, 2020)
At present, the spatial target monitoring method is mainly ground-based observation mode, and the ground-based observation mode is divided into two types: radar scattering imaging and photoelectric system imaging. In the study of imaging objects with long distances, the photoelectric imaging system has the advantages of simple calculation and low cost. However, it is difficult to realize the imaging result and the imaging effect is not ideal under the strong sky background. In response to these problems, this paper combines holographic optical imaging and reproduction technology to provide a new idea in solving the problem of atmospheric interference and achieve imaging under strong sky light background For optoelectronic imaging, this paper studies the plane wave and its optical properties including diffraction properties and holographic imaging properties from the Maxwell equations. As a holographic optical component, volume holographic grating provides a broader research platform for studying optical imaging. Volume holographic gratings have Bragg selectivity and are characterized by angular filtering and wavelength filtering. Once the wavelength of the incident light wave and the grating constant are determined, the incident angle of the light wave is unique. At this time, the incident wave satisfies the Bragg matching, and the incident light wave has the largest diffraction efficiency. When the incident light wave deviates from this angle, the diffraction efficiency drops rapidly to zero. This paper uses the Bragg characteristic of volume holographic gratings to study its diffraction efficiency distribution. Based on the analysis of diffraction efficiency, the basic parameters of volume holographic gratings are reasonably set, and the theoretical simulation experimental imaging results of volume holographic optical imaging systems are realized. In long-distance target imaging, strong sky light background has always been a research problem in the field of optics. Under the strong sky light background, the atmospheric turbulence effect is obvious, which will generate atmospheric interference, which will affect the imaging process and make imaging difficult. Therefore, a phase screen based on power spectrum inversion is adopted in this paper to simulate the effects of atmospheric turbulence. By generating a multi-layer phase screen, the target is phase shifted. In fact, the phase screen based on the power spectrum inversion method lacks low-frequency information, so low-frequency compensation is needed. The thesis solves this problem by adding two Gaussian random matrices. A verification experiment of the Bragg selection characteristics of the volume holographic grating is also performed in this paper. The two parameters of the wavelength and the incident angle are changed respectively. The theoretical imaging and interference imaging results are compared to further verify the validity of the Bragg selection characteristics. Then the work is to make a human-computer interaction visual interface of the imaging model. By entering the required wavelength and incident angle, the imaging results of each surface in the imaging system and the light intensity values received by the detector can be obtained. Finally, the article introduces the physical optics and ray tracing algorithms. According to the four-step process of ray tracing, a flat plate model is used as a numerical example, and an RCS image consistent with the theoretical value is obtained. In this thesis, in order to study the application engineering of long-range space target monitoring, a new filtering imaging model of volume holographic gratings under strong sky light interference is constructed. First, a phase screen based on power spectrum inversion is used to simulate the influence of atmospheric interference on the imaging model. But this phase screen has experimentally verified that it lacks low-frequency information. Therefore, the thesis improves its algorithm, that is, adding two Gaussian random matrices to make up for the lack of low frequency. The effect is that the imaging around the target position is more complete. Then, the thesis simulates the diffraction efficiency curve of the volume holographic grating. The thesis reasonably sets the basic parameters of the volume holographic grating, phase screen and signal wave by the curve. Finally, the thesis simulates the imaging of the volume holographic grating surface, lens surface and detector in matlab software based on the imaging model. By comparing the imaging results under ideal conditions, the thesis analyzes the imaging of each surface. Through the comparative analysis of simulation experiments, the thesis achieves the expected goals and results, and realizes the filtering imaging work under the strong sky light interference. In addition, this thesis also introduces the basic theory and calculation examples of the shooting and bouncing racy method. This work can be combined with a volume holographic grating imaging model in the future to study a more efficient imaging algorithm using the shooting and bouncing racy method.
Keywords: Photoelectric system imaging, Volume holographic grating, Bragg selectivity, Phase screen